2019
DOI: 10.1109/access.2018.2886791
|View full text |Cite
|
Sign up to set email alerts
|

Classification of 3D Archaeological Objects Using Multi-View Curvature Structure Signatures

Abstract: We propose a generalized 3D shape descriptor for the efficient classification of 3D archaeological artifacts. Our descriptor is based on a multi-view approach of curvature features, consisting of the following steps: pose normalization of 3D models, local curvature descriptor calculation, construction of 3D shape descriptor using the multi-view approach and curvature maps, and dimensionality reduction by random projections. We generate two descriptors from two different paradigms: 1) handcrafted, wherein the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…By data preprocessing, including the PCA and CM calculations, the experimental result increased 0.82%. Evidence has shown that accuracy improves using a CM when classifying archeological data [43]. Toward the improvement of feature extraction, including the FT and LSTM-RNN models [60], the accuracy of 3D microfossil model classification increased by 5.56%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By data preprocessing, including the PCA and CM calculations, the experimental result increased 0.82%. Evidence has shown that accuracy improves using a CM when classifying archeological data [43]. Toward the improvement of feature extraction, including the FT and LSTM-RNN models [60], the accuracy of 3D microfossil model classification increased by 5.56%.…”
Section: Discussionmentioning
confidence: 99%
“…Mean curvature is a single shape indicator that characterizes local variations of a surface. It is widely used in different applications, such as 3D face recognition [41], 3D skeleton shapes [42], and 3D object classification [43]. The mean curvature function is defined as follows:…”
Section: B Data Preprocessingmentioning
confidence: 99%
“…One of the most widely used applications of computational methods in human sciences is the automatic annotation and classification of large datasets (of text, images, etc. ) in digital libraries that otherwise would require a highly laborious annotation process by trained and skilled users (Canul-Ku et al, 2018;Engel et al, 2019;Dhali et al, 2020). In the case of image-based datasets, computer vision methods have been used to analyse and annotate photos e.g., the geo-reference of series of aerial photos (Cantoro, 2014), the semantic analysis of a digital library of museum artefacts, or a collection of old photographs for the semantic categorisation of contents (Eramian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…the classification of artefacts based on their shape. There is a large number of studies on this subject, those more relevant for archaeology are probably the ones by Tal (2014), Canul Ku et al (2018) Hermon et al (2018), and the research carried out in the EU-funded project GRAVITATE 11 coordinated in 2015-2018 by Michela Spagnolo of CNR (Consiglio Nazionale delle Ricerche) as well as in the AR-CHAIDE 12 EU-funded project.…”
Section: Machine Learning Text Mining and Pattern Recognitionmentioning
confidence: 99%